Nāṭṭār vaḻakkāṟukaḷil makkaḷ iṭampeyarvum varalāṟum - Tāmaraip Pāṇṭiyaṉ, Nellai Cu. (Cēkar Patippakam, 2005)
Study on the history of migration in folk literature in southern Tamil Nadu
Tamil in Tamil-Schr. - Includes bibliographical references
Keywords: Tamil Nadu; Volksliteratur; Migration